On one- and two-dimensional a–stancu–schurer–kantorovich operators and their approximation properties - Md. Heshamuddin; Rao, Nadeem; Lamichhane, Bishnu P.; Kilicman, Adem; Mursaleen, Mohammad Ayman (MDPI AG, 2022)
The goal of this research article is to introduce a sequence of α –Stancu–Schurer–Kantorovich operators. We calculate moments and central moments and find the order of approximation with the aid of modulus of continuity. A Voronovskaja-type approximation result is also proven. Next, error analysis and convergence of the operators for certain functions are presented numerically and graphically. Furthermore, two-dimensional α –Stancu–Schurer–Kantorovich operators are constructed and their rate of convergence, graphical representation of approximation and numerical error estimates are presented.